STRATEGY FOR SALES AND PROCESSING JACKFRUIT INTO INNOVATIVE CHIPS AS AN EFFORT TO IMPROVE THE ECONOMY OF THE COMMUNITY IN GAMPONG LAMBHUK, BANDA ACEH CITY - Tuwisna; Fandi Bachtiar; Sri Maisarah; Rezky Vinte Nate (RADJA PUBLIKA, 2026)
This product not only has a longer shelf life but can also be developed with various flavors and attractive packaging, thus offering potential for penetration into both local and national markets.The innovative strategy of processing jackfruit into chips is expected to provide economic benefits to the people of Gampong Lambhuk. By empowering small and medium enterprises (SMEs) and involving the community in production, marketing, and distribution, this product is expected to create job opportunities, increase income, and strengthen the local wisdom-based economic sector. According to Philip Kotler and Kevin Lane Keller in their 2019 book